Osteoactivin Promotes Migration of Oral Squamous Cell Carcinomas. Issue 8 (8th February 2016) - Arosarena, Oneida A.; dela Cadena, Raul A.; Denny, Michael F.; Bryant, Evan; Barr, Eric W.; Thorpe, Ryan; Safadi, Fayez F.
Abstract : Nearly 50% of patients with oral squamous cell carcinoma (OSCC) die of metastases or locoregional recurrence. Metastasis is mediated by cancer cell adhesion, migration, and invasion. Osteoactivin (OA) overexpression plays a role in metastases in several malignancies. The aims were to determine how integrin interactions modulate OA‐induced OSCC cell migration; and to investigate OA effects on cell survival and proliferation. We confirmed OA mRNA and protein overexpression in OSCC cell lines. We assessed OA's interactions with integrins using adhesion inhibition assays, fluorescent immunocytochemistry and co‐immunoprecipitation. We investigated OA‐mediated activation of mitogen‐activated protein kinases (MAPKs) and cell survival. Integrin inhibition effects on OA‐mediated cell migration were determined. We assessed effects of OA knock‐down on cell migration and proliferation. OA is overexpressed in OSCC cell lines, and serves as a migration‐promoting adhesion molecule. OA co‐localized with integrin subunits, and co‐immunoprecipitated with the subunits. Integrin blocking antibodies, especially those directed against the β1 subunit, inhibited cell adhesion ( P = 0.03 for SCC15 cells). Adhesion to OA activated MAPKs in UMSCC14a cells and OA treatment promoted survival of SCC15 cells. Integrin‐neutralizing antibodies enhanced cell migration with OA in the extracellular matrix. OA knock‐down resulted in decreased proliferation of SCC15 and SCC25 cells, but did not inhibit cell migration. OA in the extracellular matrix promotes OSCC cell adhesion and migration, and may be a novel target in the prevention of HNSCC spread. J. Cell. Physiol. 231: 1761–1770, 2016. © 2015 Wiley Periodicals, Inc. Abstract : Osteoactivin (OA) overexpression plays a role in metastasis in several malignancies. OA is overexpressed in oral squamous cell carcinoma cell lines and serves as a migration‐promoting adhesion molecule. OA knock‐down inhibited cellular proliferation.